Factors that influenced employees’ performance that need to be known by the business owner - Kamaruddin, Kardina; Ali, Noor Malinjasari; Borhanuddin, Rahayu Izwani; Mokhlas, Hasmi (Universiti Teknologi MARA, Terengganu, 2022)
A business owner or an entrepreneur is the one who own the company. As the owner expands its business, he or she need to employ more workers. It is not easy to manage a large numbers of workers, therefore the business owner need to know what are the factors that influenced the workers or employees’ performance?